Tren dan Aplikasi Penelitian Pendidikan - Dita Adinda Fitri; Meyniar Albina (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the trends and applications of technology in educational research, which are rapidly evolving along with digital advances and the need for adaptive learning. Phenomena such as big data, artificial intelligence (AI), and online learning have changed the way research is conducted, both in terms of data collection and analysis. Through a qualitative descriptive approach, this study analyzes various applications that support the effectiveness of educational research and the challenges faced in their use. The results show that trends such as the use of AI, big data, and mixed methods contribute significantly to the validity and efficiency of educational research. However, challenges such as low technological literacy, data security risks, and infrastructure limitations remain major obstacles. These findings are expected to be the basis for formulating data-based educational policies and developing more innovative research methods.